ORTHOGRAPHIC ERROR ANALYSIS IN WRITING AT-TARBIYAH ISLAMIC BOARDING SCHOOL SUKABUMI - Makmur, Muhammad Jibril Fladizqy; Isandi, Muhammad Ridho Ali; Muhaimin, Abdul; Andira, Muhammad Farhan; Marasabessy, Abdul Rais; Azzam, Ahmad Fadillah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Understanding and addressing writing errors is crucial for Arabic language teachers to enhance students' proficiency. This study focuses on analyzing orthographic writing errors made by seventh-grade students at the At-Tarbiyah Islamic Boarding School Sukabumi. Employing a qualitative descriptive approach, data on orthographic errors were collected through students’ responses to essay tests in Arabic language and Tajweed subjects. Additionally, interviews with Arabic and Tajweed teachers were conducted to identify the causes of these errors and propose solutions. The findings reveal that despite being in a linguistic environment, seventh-grade students frequently make orthographic errors due to several factors: the absence of a writing-focused subject in the curriculum, mishearing vocabulary, reliance on auditory input without verification, failure to review vocabulary, incorrect assumptions about word equivalencies, and visual impairments. To address these issues, the study recommends implementing targeted strategies, including increasing writing practice, training students to listen accurately to Arabic words, improving pronunciation skills, consistently reviewing previously learned vocabulary, utilizing dictionaries, and incorporating supportive teaching aids. These interventions aim to reduce orthographic errors and foster better writing skills among students. The study underscores the importance of systematic error analysis in identifying challenges and enhancing Arabic language education.